-

  

. - . .: 1961. - 248 .

- , . , - .




I.
2.
3.
4. ( )
II. -
2.
3.
4.
5.
6. ,
III.
2. (3.4)
3. (3.1)
4. 2
5. 3
6.
7.
8.
9. (x, k)-
10.
IV. -
2. (x, k)- (a, b)-
3.
4. ,
5. ,
6. , .
7.
V. -
2. (0, k)- a, b, c d
3. (0, k)- b = 0
4. (0, k)- b != 0
5.
6.
7. , .
VI. -
2. y'(t)-1/(2k)[y(t+1)-y(t-1)] = 0
3. y(t)-2ay(t-1)+by'(t-2) = 0
4. ...
5. ...
6. y'(t)+ty(t)-ey(t-e) = 0
7.
VII. - ()
2. 2y'_k(t)-y_k+1(t)-y_k-1(t) = w_k(t)
3. y'_k(t)-y_k+1(t) = w_k(t)
4. y'_k(t)-y_k-1(t) = w_k(t)
5. 2y''_k(t)-y_k+1(t)-y_k-1(t)+2ly_k(t) = w_k(t)
6. y''_k(t)-y_k+1(t)+y_k(t) = w_k(t)
7. y''_k(t)-y_k-1(t)+y_k(t) = w_k(t)
8. y''_k(t)-y_k+1(t) = w_k(t)
9. y''_k(t)-y_k-1(t) = w_k(t)
10. y(iv)_k(t)+y''(t)-0.5l[y_k+1(t)-2y_k(t)+y_k-1(t)] = w_k(t)
11. P(d2/dt2)y_k(t) = A_k*y_k+1(t)+B_k*y_k(t)+C_k*y_k-1(t)
VIII. , -
3.
4.
5.
6.
IX. -
2.
3.
4. f(Y, t)
5.
6.
7.
8.
9.
X. - . IX
2. '(t)-ay(t) = -ey^3(t)
3.
4. y'(t)+by(t-1) = ey^3(t-1)
5.
6. ...
XI.
3.
4.
5.
. -
2. -
3.
4.
5.
6. m >= n
7. m n
.